Short-term prophylaxis with ciprofloxacin in extended 16-core prostate biopsy - Chambó,Renato Caretta (2015)
Objective To evaluate the safety, efficacy and possible complications of 16-core transrectal prostate biopsies using two doses of ciprofloxacin for prophylaxis of infectious complications. Materials and Methods Sixteen-core prostate biopsies were performed on a number of patients with different signs of potential prostate cancer. Complications were assessed both during the procedure and one week later. After the procedure, urine samples were collected for culture. The rate of post-biopsy complications, hospital visits and hospitalizations were also analyzed. Ciprofloxacin (500 mg) was administered two hours before, and eight hours after the procedure. Results The overall rate of post-biopsy complications was 87.32%, being 5.4% of those considered major complications due to hemorrhage, or to urinary retention. Eight patients required hospital treatment post-biopsy. Fever occurred in just one patient (0.29%). There was no incidence of orchitis, epididymitis, prostatitis, septicemia, hospitalization, or death. The urine culture showed positive results in five patients (2.15%). Conclusion One-day prophylaxis with ciprofloxacin proved to be safe and effective in the prevention of infectious complications following 16-core prostate biopsies.